Régimen patrimonial de los matrimonios internacionales. Ley aplicable y pactos permitidos en el derecho internacional privado - Delgado Menéndez, María del Carmen (2022)
The growing number of “international” marriages, with nationalities, domiciles and properties that link the spouses with various countries, and that generate patrimonial relations both between the spouses and with third parties, highlights the importance of the issue related to the patrimonial economic regime of such marriages. This situation demands our attention to the rules of private international law which will be the basis to determine what is the law applicable to the economic patrimonial regime of an international marriage, since it is precisely this law that will define, among others, which is the patrimonial regime that governs each marriage, what are the effects of said regime, what are the permitted covenants and arrangements allowed between the spouses in this matter, as well as the legal ways for the spouses to change the current regime today. In this article we refer particularly to what international marriages must take into account in order to determine what law is applicable to their property regime, which are the most widely applied patrimonial economic regimes around the world and what are the main similarities and differences between these regimes. We illustrate the importance of this theme by relating it to increasingly frequent circumstances in which spouses repeatedly change the place of the marital domicile, involving various countries and generating a series of questions regarding the law that will be applied in order to determine which property regime governs them, what are the main characteristics and effects of said regime, as well as the legal means to which the spouses can utilize to modify said regime. As an example, we resort to the assumption of an international marriage that binds Spain and Peru, as it composed of spouses who had their first domicile in Madrid, Spain, and today reside in Lima, Peru. We indicate what is the connecting factor provided for in the Peruvian norms of private international law so as to determine which is the law regulating the patrimonial regime of an international marriage. We also refer to the property regimes of marriages provided in both the Peruvian and the Spanish legislation, including their characteristics and effects and the existing legal means for the spouses to modify said regime. Finally, some specific proposals for regulatory modification are formulated and aimed at providing Peru with a regulatory framework that provides greater predictability and legal certainty to the property regimes of international marriages.